Policy decisions and institutional change effects of Brazilian footwear industry internationalization - Halberstadt, Ismael Alan; Hahn, Ivanete Schneider; Scherer, Flavia Luciane (Revista de Negócios, 2024)
This article focuses on analyzing the main policy decisions that resulted in institutional changes and their effects in the internationalization process of the Brazilian footwear industry. A longitudinal documentary research was carried out and we used as sources government bases (IBGE and MDIC), representative entities of the industry, Comex Stat - MDIC, UNCTAD, Abicalçados website, and others. We used the last 30 years (1988-2018) as a time frame. The main findings are that: (1) the decisions of the federal government such as opening the Brazilian market to foreign products / reducing import tax rates, the implementation of The Real Plan, anti-dumping policies, payroll tax exemptions, and Brazilian Labor Reform have an impact on the internationalization of the footwear industry; (2) the internal competition generated by the actions of the state governments shows itself capable of impacting the location of the production centers and the displacement of the primary footwear exporting agents. Managers should evaluate the political environment (in-state and country-level) before the relocation of manufacturing plants, given that tax incentives and opportunities for cheap labor can benefit the industry competition in looking international markets. This paper contributes to the understanding of the impact of critical factors related to the trajectory market up to the 1990s (Fleury and Fleury, 2011).